Raspberry Pi for beginners : 2022 complete course (Packt Publishing, 2022)
Learn Raspberry Pi with the help of a step-by-step approach from scratch. This course focuses on the "why" and makes you much more autonomous, a problem solver, and adept at engineer-level thinking skills with your Raspberry Pi. About This Video This is a step-by-step, hands-on, and no copy and paste course on Raspberry Pi from scratch Look at best practices and learn how to be more independent when working on your future projects Master your Raspberry Pi with the help of hands-on practice exercises, 11 activities, and a final project In Detail You may be just getting started or have already started to learn how to build projects with your Raspberry Pi. But knowing what to do first and which path to follow can be quite hard, and you may feel stuck. This course is not a course where you just download some code and run it. This is a course where you will truly understand how to write the code and work with the different Raspberry Pi functionalities. The course will start with setting up your Raspberry Pi and installing Raspberry Pi OS without an external monitor and keyboard, followed by getting along with the basics of Python3 programming. You will then work with the Raspberry Pi's GPIO panel, use a PIR sensor to detect movement from your Pi, and discover how to use a Unix terminal and the most useful command-line tools. You will also send an email from your Raspberry Pi, take photos and videos using the Raspberry Pi camera V2, and create a web server on your Raspberry Pi with the Flask framework. Finally, you will build a complete surveillance and alarm project with Raspberry Pi. By the end of the course, you will have a strong foundation with Raspberry Pi, and you will be able to start your own projects in no time. This course is not for you if you prefer a quick copy/paste solution or if you are already an advanced Raspberry Pi user. Audience This course is for students, engineers, researchers, teachers, developers, hobbyists, and anyone wanting to learn how to get started with Raspberry Pi and build amazing projects. Any individual who understands what they are doing with Raspberry Pi, Python 3, and the different components you can use with the board will be highly benefitted from this course. You will need a computer + a Raspberry Pi 4 (also works with Raspberry 2 and 3), along with SD card Class 10, PIR sensor HC-SR501, and Raspberry Pi camera V2. No external monitor or keyboard, no programming, Unix, or hardware experience is required.